Mapping acquisition of loading loss coefficient of main driving system of machine tools. (July 2016) - Xie, Jun; Liu, Fei; Huang, Jing; Qiu, Hang
The machining systems that mainly consist of machine tools are numerous and are used in a wide range in industries. The total amount of energy consumption by machining systems in the world is extremely high. The loading loss energy is one of the most important and complicated parts of the energy consumption of machine tool in machining processes. The key of acquiring the loading loss energy is the acquisition of the loading loss coefficient, which is indispensable for machine tools' energy efficiency on-line monitoring, energy prediction and energy quota customization. Up to now, the loading loss coefficient is mainly obtained by the experimental method which needs to conduct a large amount of experiments and a comprehensive on-line measurement to obtain the input power, idle power and cutting power beforehand. On the other hand, in many cases, it is unavailable to install the dynamometers on the machine tool's worktable to measure the parameters on-line. This article provides a mapping method to acquire the loading loss coefficient of main driving system of machine tools. First, choose a standard machine tool, cutter and workpiece to construct the standard machining circumstance. Second, carry out the experiments with a series of given cutting parameters under the standard circumstance and record the cutting power accordingly. Third, construct the overall cutting power model which can be used to calculate the cutting power of any other target machine tools under the standard machining circumstance. Fourth, establish the air-cutting power database of the target machine tools. Then, carry out the experiments on the target machine tool with the parameters which is as close as possible to the standard parameters and record the input power of the main driving system respectively. Finally, substitute the input power, air-cutting power and cutting power into the acquisition model to calculate the loading loss coefficient. The case study indicates that this method with high accuracy, on the other hand, can simplify the procedure of the acquisition of the loading loss coefficient to a great degree and shows that the method is practical and promising.